Development of a capacitive deionization (CDI) device for water desalination - Ng, Colin (2017)
Clean water is linked to global energy supply and global warming. Today, clean water is still not available to one out of seven people globally. 90% of desalination plants worldwide utilise reverse osmosis (RO) or multistage flash distillation (MSF) for desalination. Both processes require either high water pressures or heating. Capacitive deionization (CDI) is a relatively new form of desalination technology which is promising as it can consume less energy than both RO or MSF in certain conditions. Much more research into CDI has been done in recent years and this trend is expected to continue. In this final year project, the design, fabrication, and experimentation of a CDI cell was performed. After careful design and fabrication were completed, testing was done to ensure zero leakage of the cell. Experiments were then conducted, with the aim of studying the effect of the spacer channel shape on CDI cell performance. By delivering a salt solution between two charged carbon electrodes with a potential difference of 1.2V, salt would be adsorbed into the electrodes, delivering water with a lower salinity in the effluent stream. As salinity is directly proportional to conductivity, inlet water and effluent water conductivity was tested to determine any changes in salinity. The expected result was for a torturous path spacer channel to increase the desalination capabilities of the CDI cell, but results proved this to only be true for the first few minutes of operation. After salinity levels had reached equilibrium, the total removed salt molecules were less in the CDI cell with the torturous path spacer than in the one with a regular spacer.